The challenges of teaching biology through the medium of English: the case of Jim Chavane High School, Limpopo Province - Maluleke, M'zamane Johannes (My University, 2007)
The study sought to investigate the challenges which teachers and learners encountered on daily basis when they use English as the medium of instruction (MOI) in content subjects. The study was conducted at Jim Chavani High school which was convenient for the researcher who is a deputy principal of the school. The researcher has purposively selected Biology which is regarded as one of the most difficult subjects and which has high failure rate in most schools in the Malamulele area. The literature review was obtained from a variety of sources which include library books, journals, government gazettes, news papers and the internet. The review shed light on the challenges of teaching through the medium of English among learners with indigenous language backgrounds. This body of research has shown that attention was placed on townships and urban areas with little or no focus on remote rural areas such as Malamulele. The researcher used the qualitative research methodology to collect data through classroom observations, interviews, and writing protocols.The use of qualitative enquiry enabled the researcher to explore the challenges in a natural setting. Three teachers and eighteen learners were respondents in the study. Data collected were discussed and analysed in order to select the most suitable information which could address the aim and objectives of the study. The result of the study showed that the learners were negative towards the use of English as the MOI. On the converse, the teachers have mixed feeling on the choice for English even though they acknowledge difficulties iv posed by English in their classrooms. Spoken data showed a varied degree of code-alternation and culturally induced strategies were found in their writing protocols. Given these findings, the study draws a conclusion that using English as the MOI in remote rural areas further disadvantages the learners from getting the full benefits for comprehension in the content subject. It was therefore recommended that language planners needed to step up the process of allowing indigenous African languages as the media of learning while English is taught as the school subject.
Thesis (M.A. (English)) --University of Limpopo (Turfloop Campus), 2007
Keywords: Biology teaching, english; Biology -- Study and teaching (Secondary) -- South Africa